A renewable energy system for a nearly zero greenhouse city: Case study of a small city in southern Italy. (15th January 2018) - De Luca, G.; Fabozzi, S.; Massarotti, N.; Vanoli, L.
Abstract: This paper presents an economic and energy feasibility analysis of a renewable energy system for a small city in southern Italy to convert it to zero greenhouse gas city by 2030. The proposed energy infrastructure utilises different technologies: wind turbine, photovoltaic panels and biogas cogeneration plants to produce electric energy, and thermal solar panels, cogeneration and heat pumps to meet the thermal energy demand of the city. The electrification of transport sector is also considered. The whole city energy system is analysed by the EnergyPLAN software to evaluate streams combination and potential synergies between the different sectors. In order to improve the analysis, PhotoVoltaic technology has been simulated in TRNSYS environment, to obtain detailed prediction of this component of the energy infrastructure. The system behaviour was analysed considering different time bases: daily, weekly and yearly. The EnergyPLAN outputs include the aggregated yearly production and demands of all modelled energy conversion systems, as well as hourly values useful to identify the measures to make Altavilla Silentina nearly zero carbon city. Every measure identified becomes a new input in EnergyPLAN to evaluate its effect on city energy balance. The economic analysis has been performed to evaluate the electricity and thermal energy costs.